Evaluación del nivel de conocimiento de carcinoma oral de células escamosas en la atención clínica odontológica. (2021)
Oral squamous cell carcinoma (COCE) is a malignant neoplasm, which originates from the squamous cells of the epithelium that covers the oral mucosa, it is the most frequent.